Pengaruh Partisipasi Anggaran, Komitmen Organisasi, Motivasi Terhadap Kinerja Manajerial Pada Perusahaan Pt. Zzz - Jonathan Jonathan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research aims to determine the effect of budget participation, organization’s commitment and motivation toward managerial performance. The population included was employees in beverage company in Jakarta. Sampling was collected by using a purposive sampling method and the number of sample obtained 139 samples that meet the criteria and free from outliers. In addition to the above primary data, this study also collected secondary data from literatures and studies. Multiple Regression analysis was used as analytical technique. The result showed that budget participation, organization’s commitment and motivation jointly have significant positive effect on managerial performance. The study therefore recommends among others that all those presently involved in the implementation of budgets should be educated on the purpose and objectives of budgetary control and that lower level managers and staffs who are directly involved in the implementation of the budget should be co-opted into the budget setting process.